A Reliable and Efficient MAC Protocol for Underwater Acoustic Sensor Networks. (4th October 2011) - Xiong, Junjie; Lyu, Michael R.; Ng, Kam-Wing
Abstract : Underwater acoustic sensor networks (UWASNs) are playing a key role in ocean applications. Unfortunately, the efficiency of UWASNs is inferior to that of the terrestrial sensor networks (TWSNs). The main reasons are as follows: (1) UWASNs suffer long propagation delay; (2) UWASNs are limited by the narrow bandwidth. Many MAC protocols are proposed to improve the efficiency of UWASNs. However, their improvement is not enough. Moreover, few of them consider the reliability of UWASNs even though the packet loss can fail the applications. Actually, a few of the protocols employ the traditional acknowledgment (ACK) mechanism, but they suffer the throughput degradation a lot. In this paper, first, we propose a protocol called RAS, a priority scheduling approach for multihop topologies. RAS is more efficient in throughput and delay performance. Then, we propose a reliable RAS called RRAS that obtains a tradeoff between the reliability and the efficiency. RRAS designs an ACK and retransmission mechanism, that is, different from the traditional one so that it can maintain a comparable throughput when improving the reliability. Extensive evaluations are conducted to verify that RAS is efficient and RRAS is a tradeoff on reliability and efficiency.